A Short Review on Synthesis, Characterization, and Applications of Zeolites - Tessema Derbe; Shewaye Temesgen; Mamaru Bitew (Advances in Materials Science and Engineering)
The review emphasizes on synthesis, characterization, and application of zeolite. Zeolite is a hydrated aluminosilicate having a tetrahedral structural framework; it contains channels and cages which are occupied by exchangeable active metal ions and water molecules. Zeolite was synthesized through different synthesis methods, particularly, hydrothermal and green synthesis methods. The review also has tried to address the structure of zeolite such as morphology, functional group, and particle size using different characterization methods as reported via different authors. The characterization results verify that zeolite shows many unique properties such as uniform pore size, acidic properties, thermal stability, mobile extra cation, hydrophilicity, and hydrophobicity. These lead to a number of applications in catalysis, water purification, adsorption, and agriculture.